Exchange stiffness influence on Terfenol-D magnetic states. Issue 1 (1st October 2018) - Chen, Cai; Fu, Brian D; Dannecker, Marina E; Curiel, Rodrigo U; Carman, Gregory P; Sepulveda, Abdon E
Abstract: Terfenol-D has one of the largest magnetoelastic coefficients at room temperature, making it a good candidate for future magnetoelectric memory devices. However, few studies exist on the spin configuration in nanoscale Terfenol-D single domain structures. There are two exchange stiffness parameters of Terfenoal-D reported in the literature. In this paper, we use micromagnetic simulations to evaluate the influence of these two exchange parameters on the spin states of ellipsoidal shapes. Analytical results indicate that these two parameters produce significantly different spin states. Therefore, experiments to more accurately measure the exchange stiffness constant of Terfenol-D are needed.